Local Vibrio Isolates Exhibit Molecular Characteristics Distinct from Reference V. harveyi and V. campbellii Strains - Cortado, Hanna; San Luis, Boris; dela Peña, Leobert; Monsalud, Rosario; Hedreyda, Cynthia (Science Diliman: A Journal of Pure and Applied Sciences; Vol 17 No 1 (2005), 2007)
Six Vibrio isolates identified biochemically as Vibrio campbellii from Southeast Asian Fisheries Development Center (SEAFDEC) in Tigbauan, Iloilo, were characterized by 16 rDNA sequence, total protein profile, and DNA profile analyses. Genomic DNA from the isolates were subjected to PCR using four sets of primers targeting gene fragments of hemolysin and toxR based on sequences from reference Vibrio harveyi (IFO15634), V. campbellii (IFO1563), and local isolates identified as V. harveyi. Total protein profile could not distinguish the isolates from one another and from the reference V. harveyi (IFO15634) and V. campbellii (IFO15631). Analysis of 16s rDNA sequences revealed high degree of sequence similarity (96% - 99%) of the six local isolates with other Vibrio species including V. campbellii and V. parahaemolyticus, indicating that this analysis will not be useful in resolving their identity. All six isolates exhibited characteristic reference V. harveyi PCR profile when a primer set designed to amplify a 308-bp fragment of hemolysin gene in that species was used. However, no amplicons were generated for these isolates using primers that amplify toxR gene fragments in V. harveyi. This suggests that the six isolates were not bonafide V. harveyi strains. The isolates also did not exhibit V. campbellii characteristics since the primer designed to target the toxR gene in V. campbellii could not amplify DNA from any of the six isolates, suggesting that they were not bonafide V. campbellii strains either. The toxR gene from the six isolates could be amplified using a primer based on toxR gene sequences from a SEAFDEC isolate previously identified as V. harveyi (PN-9801). These data suggest that the six isolates previously identified as V. campbellii as well as PN-9801 may be classified in one group separate from bonafide reference V. harveyi and reference V. campbellii strains, based on the identical results in the molecular analyses performed in this study.